2005
DOI: 10.1590/s1517-83822005000400001
|View full text |Cite
|
Sign up to set email alerts
|

Field persistence of Bacillus thuringiensis on maize leaves (Zea mays L.)

Abstract: The persistence slope of Bacillus thuringiensis (Bt) based products in the field is an important parameter to evaluate their efficacy. The half-life, estimated based on persistence slope parameters, is one of the most effective tools to select microbial pesticides. The aim of this research was to study the relationship between viability loss of Bt spores on maize leaves and their concentration, comparing it with field persistence. The experimental design was split-plot on time, composed by maize plants, in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Other studies showed the persistence of spores of Bacillus sp. in soil for months or years; this data clearly indicates that soil is a favorable reservoir for viable spores, whether the soil is in a rural or urban environment ( 16 , 17 ). It is also possible that these bacteria use some soil natural components, such as nutrients; according to literature reports, B. thuringiensis BT27a grew in artificial soil with humic acid as the sole carbon and energy source ( 18 ).…”
Section: Discussionmentioning
confidence: 88%
“…Other studies showed the persistence of spores of Bacillus sp. in soil for months or years; this data clearly indicates that soil is a favorable reservoir for viable spores, whether the soil is in a rural or urban environment ( 16 , 17 ). It is also possible that these bacteria use some soil natural components, such as nutrients; according to literature reports, B. thuringiensis BT27a grew in artificial soil with humic acid as the sole carbon and energy source ( 18 ).…”
Section: Discussionmentioning
confidence: 88%
“…The relatively high persistence of the toxic effects of B. thuringiensis in comparison to data available in the literature (CASTELO BRANCO, 1999;HADDAD et al, 2005) suggests that the performance of this bioinsecticide is less affected by weather conditions in the subtropics than in warmer tropical areas, where solar radiation is described as affecting the persistence of the spores of B. thuringiensis (POLANCZYK & ALVES, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Other lepidopteran larvae that ingest sublethal doses of Bt also resume normal development after a few days (Moreau and Bauce, 2003;Siegfried et al, 2001). Dutton et al (2005a) reported that there were no significant effects on overall larval development when 3 rd instars of S. littoralis larvae were exposed to Bt sprayed plants because the effect of the toxin did not persist for long due to rapid degradation of the Bt spray (Haddad et al, 2005). In contrast, significant effects, attributed to long toxin persistence, were reported when larvae were reared for four days on Bt maize (Haddad et al, 2005 (Horner et al, 2003;Stewart et al, 2001) and D. plexippus (Dively et al, 2004).…”
Section: Effect Of Bt Maize On Stem Borer Development and Mortalitymentioning
confidence: 99%
“…Dutton et al (2005a) reported that there were no significant effects on overall larval development when 3 rd instars of S. littoralis larvae were exposed to Bt sprayed plants because the effect of the toxin did not persist for long due to rapid degradation of the Bt spray (Haddad et al, 2005). In contrast, significant effects, attributed to long toxin persistence, were reported when larvae were reared for four days on Bt maize (Haddad et al, 2005 (Horner et al, 2003;Stewart et al, 2001) and D. plexippus (Dively et al, 2004). Development time of the 5 th instar of C. partellus larvae subjected to transient feeding on Bt maize at the same growth stage was not affected (Obonyo et al, 2008b), possibly because pupation follows shortly after the 5 th larval stage in this species at which time the larvae are relatively inactive and do not feed much (Tettamanti et al, 2007); and their large sizes enable them to tolerate more toxin (Huang et al, 1999).…”
Section: Effect Of Bt Maize On Stem Borer Development and Mortalitymentioning
confidence: 99%